Tracking The Death Of The Iranian President In BBC 'Arabi News Reports: A Critical Analysis From Norman Fairclough's Perspective - Dhihyah Dhihyah; Abdul Basid (Universitas Cokroaminoto Palopo, 2024)
This study aims to uncover: 1) text analysis dimensions in news about the death of the President of Iran and his entourage, 2) discourse practice dimensions in the same news, and 3) sociocultural dimensions within this news. Data collection techniques included observation, reading, and recording, analyzed using Miles and Huberman's method: data reduction, data presentation, and conclusion drawing. The study found that: 1) in text analysis, sentence structure and vocabulary highlight the news as both a tragedy and a trigger for international reactions; 2) in discourse practice, it was noted that BBC news disseminated information from the Iranian News Agency (IRNA), an official Iranian channel; 3) in sociocultural practice, the death signifies enhanced solidarity between Iran and other countries. In the news of the death of the Iranian President and his entourage, it can be seen that the level of solidarity between Iran and other countries is very high and the emergence of various subjective accusations against the US, which has a background of tensions with Iran in the past, this affecting this tragedy.